PENGARUH TERAPI KOGNITIF TERHADAP CITRA TUBUH KLIEN ULKUS DIABETIK - Nur Anisah; Budi Ana Keliat; Ice Yulia Wardani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
ABSTRACTDiabetic ulcers are chronic complications in diabetes mellitus so that the high risk of infection and diabetic amputasi can cause the client to feel hopeless and unable to accept circumstances that can affect self-concept but it also affects biological and social. The research objective was to determine the effect of cognitive therapy on body image clients diabetic ulcers. The research method uses a quantitative approach to design quasy Experimental Pre-Post with Control Group. Respondents number 62. Respondents were selected by purposive sampling. The collection of data through questionnaires on the client diabetic ulcers. The results showed that body image, self-esteem, ulcer conditions changed for the better as well as the ability to think positively and capability of treating clients be granted increased signiﬁ kan.after nurses nursing actions, cognitive therapy and family psychoeducation on body image of diabetic ulcers clients to make more optimal, but it needs to be improved both in the clinic and at home community wounds.